A Neoproterozoic arc-backarc system in the northern Yangtze Block: Implications for crustal growth and Rodinia reconstructions - Chao Chen; Hao Deng; Jin-Ling Yuan; Timothy Kusky; Qiang Chen; Zhen-Bing She; Ling-Yao Kong; Jiang Zhu; Hong-Mei Li; Jing-Meng Huang; Guo-Hu Wang; Cheng Yang; et al. (Earth-Science Reviews, 2026)

Gold and REE pre-enrichment in metasomatized Archean lithospheric mantle aided the genesis of Mesozoic giant ore deposits, eastern North China Craton - Shan-Shan Li; Kun-Feng Qiu; Timothy Kusky; Lu Wang; Hartwig E. Frimmel; Yi-Xue Gao; Tong Zhou; Deng-Yang He; Hao-Cheng Yu; Zheng-Yu Long; Tian-Shuo Liang; Ying-Jiu Wang; et al. (Earth-Science Reviews, 2026)

In-Season monitoring of rice phenology for massive germplasm resources using Explainable Machine learning and a Transformer CNN model - Xiaoxu Han; Yangyang Gu; Hengbiao Zheng; Di Wang; Fangming Wu; Meng Zhou; Hongxu Ai; Timothy A. Warner; Chongya Jiang; Tao Cheng; Yongchao Tian; Yan Zhu; et al. (Computers and Electronics in Agriculture, 2026)

Combining the time-series of vegetation index during the optimal window with dynamic canopy physiological features for soybean grain protein prediction - Mingrui Zhang; Wei Li; Jinxin Tang; Yangming Zhang; Timothy A. Warner; Chongya Jiang; Hengbiao Zheng; Tao Cheng; Yongchao Tian; Yan Zhu; Weixing Cao; Xia Yao (ISPRS Journal of Photogrammetry and Remote Sensing, 2026)

Association between ambient air pollution and colorectal cancer risk: The Multiethnic Cohort Study - Ugonna Ihenacho; Chiuchen Tseng; Jun Wu; Scott Fruin; Timothy V. Larson; Salma Shariff-Marco; Loïc Le Marchand; Daniel O. Stram; Brian Z. Huang; Lynne R. Wilkens; Christopher A. Haiman; Beate Ritz; et al. (Environmental Research, 2026)

Ensuring consistency in spatially-stratified stock assessment models: An analytical solution for equilibrium population structure with connectivity for age-and size-structured models - Matthew LH. Cheng; Timothy J. Miller; Daniel R. Goethel; Curry J. Cunningham (Fisheries Research, 2026)

Identifying Ancient Zircon Provenances Using a Domain-Adversarial Neural Network - Mengwei Zhang; Guoxiong Chen; Timothy Kusky; T. Mark Harrison; Lu Wang; Qiuming Cheng (Mathematical Geosciences, 2026)

The Sedimentary Geochemistry and Paleoenvironments Project Phase 2 data release: An open data resource for the study of Earth's environmental history - Úna C. Farrell; Hunter C. Olson; Maya O. Thompson; Michelle L. Abshire; Oyeleye O. Adeboye; Anne-Sofie C. Ahm; Lewis J. Alcott; Thomas J. Algeo; Ross P. Anderson; Arif H. Ansari; Lucas Pinto Heckert Bastos; Kohen W. Bauer; et al. (Chemical Geology, 2026)

The drying kinetics of various pulses: Connecting the scaling method for fluidised beds and the concept of a Characteristic Drying Curve - Min Wu; Shu Cheng; Timothy A.G. Langrish (Food and Bioproducts Processing, 2026)

Microplastic fibers and leachates from cigarette butts: environmental impacts, toxicological concerns, and circular economy-driven solutions - Aderemi Timothy Adeleye; Md Mezbaul Bahar; Mallavarapu Megharaj; Cheng Fang; Mohammad Mahmudur Rahman (Environmental Research, 2026)

Levels of 129I in coastal Pacific Ocean waters from southern California, 2011–2020 and the legacy of Fukushima - A. J. Timothy Jull; Ching-Chih Chang; George S. Burr; Li Cheng; Joellen Russell; Mang Lin; Daniel R. Crocker; Mark Thiemens; Dana Biddulph; Marc W. Caffee; Tom Woodruff; Christopher Glynn; et al. (Frontiers in Marine Science, 2026)
The Fukushima Daiichi Nuclear Power Plant accident released radionuclides directly into the ocean as a result of the Great East Japan Earthquake on March 11, 2011. This material has been transported across the Pacific Ocean and detected in the northeastern Pacific. We began a surface ocean 129 I monitoring program a few months after this disaster in June 2011, with samples from Scripps Pier, La Jolla, California, USA, with the expectation that surface currents originating off the east coast of Japan could eventually carry radionuclides to the La Jolla site. We could not identify a significant distinct signal that can be traced to Fukushima from the record from 2011-2020. We have however recorded a systematic seasonal 129 I time series record that appears to be due to surface circulation variations along the California coast, or perhaps other unexplained effects. We have reported on some of these effects previously, where we summarized results up to 2018. Since then, we have analyzed additional samples obtained during our sampling program for 2018–2020 from Scripps and also report other results collected during 2015–2016 from Newport Beach, CA, which had not been reported. These results support and expand on the previously published dataset.

The Sedimentary geochemistry and paleoenvironments project phase 2 data release: An open data resource for the study of Earth's environmental history - Úna C. Farrell; Hunter C. Olson; Maya O. Thompson; Michelle L. Abshire; Oyeleye O. Adeboye; Anne-Sofie C. Ahm; Lewis J. Alcott; Thomas J. Algeo; Ross P. Anderson; Arif H. Ansari; Lucas Pinto Heckert Bastos; Kohen W. Bauer; et al. (Chemical Geology, 2026)

Correlation of optical properties with particle size, morphology, and polymorph of fine- and nano-particle formulations of titanium dioxide powders - Schuyler P. Lockwood; Zezhen Cheng; Valentina Sola; Nurun Nahar Lata; Tanya L. Myers; Timothy J. Johnson; Mark E. Bowden; Alla Zelenyuk (Journal of Aerosol Science, 2026)

Origin and global spread of an endemic chytrid fungus lineage linked to the bullfrog trade - Luisa P. Ribeiro; Julia R. Ernetti; Joice Ruggeri; Thomas S. Jenkinson; Adeline Loyau; Helen Butler; Tina Cheng; Dirk S. Schmeller; Timothy Y. James; Luís Felipe Toledo (Biological Conservation, 2026)

The comparison between multiple linear regression and random forest model in predicting environmental noise and its frequency components level in Hong Kong using a land-use regression approach - Chui Hei Wong; Zhiyuan Li; Steve Hung Lam Yim; Ta-Yuan Chang; Chung Ling Man; Chin Ho Cheng; Timothy Chi-yui Kwok; Kin Fai Ho (Environmental Research, 2025)

Cigarette butt-derived nanocomposites: A win-win approach for microplastic removal and ecological mitigation - Aderemi Timothy Adeleye; Md Mezbaul Bahar; Mallavarapu Megharaj; Cheng Fang; Mohammad Mahmudur Rahman (Journal of Environmental Chemical Engineering, 2025)

Technical Considerations of Pharmacokinetic Assays for LNP-mRNA Drug Products by RT-qPCR - Jason Pennucci; Amanda Hays; Wendy Adamowicz; Mitra Azadeh; Mohamed Benhammadi; Enric Bertran Portabella; MingLai Cheng; Kelly Colletti; Sanjay L. Dholakiya; Rajitha Doddareddy; Lara Duchstein; Jennifer Durham; et al. (The AAPS Journal, 2025)
Lipid nanoparticle-messenger RNA (LNP-mRNA) drug products are a growing class of drug modalities. The unique composition of these drug products requires multiple measurements to account for the different components of these drug modalities. Pharmacokinetic (PK) measurements include measurement of the encapsulated mRNA and components of the LNP in circulation to understand the effectiveness of the therapeutic mRNA. The PK measurements can utilize many different platforms including PCR. Current regulatory guidance documents for bioanalytical method validation are specific to ligand binding and chromatographic assay methods and difficult to interpret for use with molecular workflows. The purpose of this paper is to provide information on considerations for validation of regulated reverse transcription quantitative PCR (RT-qPCR) assays that are used to support the pharmacokinetic analysis of LNP-mRNA drug products. Graphical Abstract

A in-seasonal phenology monitoring approach for wheat breeding accessions with time-series RGB imagery by using a combination KNN-CNN-RF model - Meng Zhou; Jie Zhu; Hongxu Ai; Yangming Zhang; Timothy A. Warner; Hengbiao Zheng; Chongya Jiang; Tao Cheng; Yongchao Tian; Yan Zhu; Weixing Cao; Xia Yao (ISPRS Journal of Photogrammetry and Remote Sensing, 2025)

Observed CO2 concentration reveals steep decrease of anthropogenic emissions in winters of 2021 and 2022 in Hangzhou and Yangtze River Delta region, China - Cheng Hu; Huili Liu; Yifan Zhang; Yu Cui; Fan Sun; Xuejing Shi; Junqing Zhang; Yanrong Yang; Leying Zhang; Bing Qi; Qitao Xiao; Ning Hu; et al. (Science of The Total Environment, 2025)

Improved generality of wheat green LAI models through mitigation of the effect of leaf chlorophyll content variation with red edge vegetation indices - Wei Li; Dong Li; Timothy A. Warner; Shouyang Liu; Frédéric Baret; Peiqi Yang; Jiale Jiang; Mingxia Dong; Tao Cheng; Yan Zhu; Weixing Cao; Xia Yao (Remote Sensing of Environment, 2025)

Revising the coal mining CH4 emission factor based on multiple inventories and atmospheric inversion approach at one of the world's largest coal production areas: Shanxi province, China - Xuejing Shi; Yiyi Peng; Shumin Wang; Yifan Zhang; Junqing Zhang; Hao Song; Yu Cui; Fan Sun; Huili Liu; Qitao Xiao; Ning Hu; Wei Xiao; et al. (Science of The Total Environment, 2025)

Multiple-model based simulation of urban atmospheric methane concentration and the attributions to its seasonal variations: A case study in Hangzhou megacity, China - Junqing Zhang; Dan Ji; Cheng Hu; Timothy J. Griffis; Qitao Xiao; Xinyue Ai; Huili Liu; Xuejing Shi; Fan Sun; Bing Qi; Wei Xiao (Environmental Pollution, 2024)

Novel 3D photosynthetic traits derived from the fusion of UAV LiDAR point cloud and multispectral imagery in wheat - Yangyang Gu; Yongqing Wang; Yapeng Wu; Timothy A. Warner; Tai Guo; Hongxu Ai; Hengbiao Zheng; Tao Cheng; Yan Zhu; Weixing Cao; Xia Yao (Remote Sensing of Environment, 2024)

Pharmacokinetic Profile of Brepocitinib with Topical Administration in Atopic Dermatitis and Psoriasis Populations: Strategy to Inform Clinical Trial Design in Adult and Pediatric Populations - Farzaneh Maleki; Cheng Chang; Vivek S. Purohit; Timothy Nicholas (Pharmaceutical Research, 2024)
Introduction Topical brepocitinib, a tyrosine kinase (TYK)2/Janus kinase (JAK)1 inhibitor, is in development for psoriasis (PsO) and atopic dermatitis (AD). Quantitative analyses of prior clinical trial data were used to inform future clinical trial designs. Methods Two phase 2b studies in patients with AD and PsO were used to characterize the amount of topical brepocitinib and the resultant systemic trough concentration ( C Trough ) using a linear mixed-effects regression (LMER). This model was used to predict brepocitinib systemic C Trough for higher treated body surface areas (BSAs) in adults and children. Information from non-clinical and clinical trials with oral brepocitinib was leveraged to set safety thresholds. This combined approach was used to inform future dose-strength selection and treated BSA limits. Results Data from 256 patients were analyzed. Patient type, dose strength, and frequency had significant impacts on the dose–exposure relationship. Systemic concentration in patients with PsO was predicted to be 45% lower than in patients with AD from the same dose. When topically applied to the same percentage BSA, brepocitinib systemic exposures are expected to be comparable between adults and children. The systemic steady-state exposure after 3% once daily and twice daily (2 mg/cm 2 ) cream applied to less than 50% BSA in patients with AD and PsO, respectively, maintains at least a threefold margin to non-clinical safety findings and clinical hematologic markers. Conclusion The relationship between the amount of active drug applied and brepocitinib systemic C Trough , described by LMER, may inform the development strategy for dose optimization in the brepocitinib topical program.

The Unseen Threat of the Synergistic Effects of Microplastics and Heavy Metals in Aquatic Environments: A Critical Review - Aderemi Timothy Adeleye; Md Mezbaul Bahar; Mallavarapu Megharaj; Cheng Fang; Mohammad Mahmudur Rahman (Current Pollution Reports, 2024)
Purpose of Review The synergistic effects of microplastics (MPs) and heavy metals are becoming major threats to aquatic life and human well-being. Therefore, understanding synergistic interactions between MPs and heavy metals is crucial to comprehend their environmental impacts. Recent Findings The mechanisms such as electrostatic attraction, surface interactions, ion exchange, hydrogen bonding, hydrophobic forces, and π–π interactions behind the synergistic effects of MPs and heavy metals were critically reviewed and justified. In addition, the roles of surface chemistry in these interactions were also emphasized. Finally, efficient remediation techniques aligning with a circular economy-based initiative to promote sustainable solutions were recommended to mitigate plastic-heavy metal pollution to achieve a cleaner environment. Summary This review examines the combined impact of MPs and heavy metals in aquatic ecosystems, detailing their mechanistic interactions, and consequences with proposed sustainable solutions. Additionally, this review highlights the MP-heavy metal contamination risks and emphasizes the need for further research to safeguard aquatic life and human health.

Electromechanical Response of Mesenteric Ischemia Defined Through Simultaneous High-Resolution Bioelectrical and Video Mapping - Sachira Kuruppu; Leo K. Cheng; Timothy R. Angeli-Gordon; Recep Avci; Niranchan Paskaranandavadivel (Annals of Biomedical Engineering, 2024)

The relationship between wheat yield and sun-induced chlorophyll fluorescence from continuous measurements over the growing season - Jie Zhu; Yuming Yin; Jingshan Lu; Timothy A. Warner; Xinwen Xu; Mingyu Lyu; Xue Wang; Caili Guo; Tao Cheng; Yan Zhu; Weixing Cao; Xia Yao; et al. (Remote Sensing of Environment, 2023)

A paradigm shift in Precambrian research driven by big data - Zhen-Jie Zhang; Timothy Kusky; Xin-Kun Yang; Qiu-Ming Cheng (Precambrian Research, 2023)

Classification and nomenclature of volcanic rocks using immobile elements: A novel approach based on big data analysis - Mingde Lang; Zhaochong Zhang; Zhen Chen; Zhiguo Cheng; M. Santosh; Timothy M. Kusky (Lithos, 2023)

Quantitative monitoring of salt stress in rice with solar-induced chlorophyll fluorescence - Kangkang Wang; Jie Zhu; Xinwen Xu; Tongjie Li; Xue Wang; Timothy A. Warner; Tao Cheng; Yan Zhu; Weixing Cao; Xia Yao; Zhengdong Zhang (European Journal of Agronomy, 2023)

Particulate matter, traffic-related air pollutants, and circulating C-reactive protein levels: The Multiethnic Cohort Study - Meera Sangaramoorthy; Juan Yang; Chiuchen Tseng; Jun Wu; Beate Ritz; Timothy V. Larson; Scott Fruin; Daniel O. Stram; Sung-shim Lani Park; Adrian A. Franke; Lynne R. Wilkens; Jonathan M. Samet; et al. (Environmental Pollution, 2023)

Tracing the nitrogen nutrient status of crop based on solar-induced chlorophyll fluorescence - Yuming Yin; Jie Zhu; Xinwen Xu; Min Jia; Timothy A. Warner; Xue Wang; Tongjie Li; Tao Cheng; Yan Zhu; Weixing Cao; Xia Yao (European Journal of Agronomy, 2023)

Fluidized bed drying of chickpeas: Developing a new drying schedule to reduce protein denaturation and remove trypsin inhibitors - Shu Cheng; Timothy A.G. Langrish (Journal of Food Engineering, 2023)

RSARE: A physically-based vegetation index for estimating wheat green LAI to mitigate the impact of leaf chlorophyll content and residue-soil background - Wei Li; Dong Li; Shouyang Liu; Frédéric Baret; Zhiyuan Ma; Can He; Timothy A. Warner; Caili Guo; Tao Cheng; Yan Zhu; Weixing Cao; Xia Yao (ISPRS Journal of Photogrammetry and Remote Sensing, 2023)

Spatio-temporal analysis of big data sets of detrital zircon U-Pb geochronology and Hf isotope data: Tests of tectonic models for the Precambrian evolution of the North China Craton - Zhen-Jie Zhang; Timothy Kusky; Min Gao; Qiu-Ming Cheng (Earth-Science Reviews, 2023)

A systematic review and meta-analysis of non-vitamin K antagonist oral anticoagulants vs vitamin K antagonists after transcatheter aortic valve replacement in patients with atrial fibrillation - Amanda Jia Qi Ooi; Chloe Wong; Timothy Wei Ern Tan; Trina Priscilla Ng; Yao Neng Teo; Yao Hao Teo; Nicholas L. Syn; Andie H. Djohan; Yinghao Lim; Leonard L. L. Yeo; Benjamin Y. Q. Tan; Mark Yan-Yee Chan; et al. (European Journal of Clinical Pharmacology, 2022)

Aging and white matter microstructure and macrostructure: a longitudinal multi-site diffusion MRI study of 1218 participants - Kurt G. Schilling; Derek Archer; Fang-Cheng Yeh; Francois Rheault; Leon Y. Cai; Colin Hansen; Qi Yang; Karthik Ramdass; Andrea T. Shafer; Susan M. Resnick; Kimberly R. Pechman; Katherine A. Gifford; et al. (Brain Structure and Function, 2022)

Correction to: 2021 Taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Bernard R. Agwanda; Rim Al Kubrusli; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Christopher F. Basler; et al. (Archives of Virology, 2021)

2021 Taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Bernard R. Agwanda; Rim Al Kubrusli; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Christopher F. Basler; et al. (Archives of Virology, 2021)

Genetic analyses of gynecological disease identify genetic relationships between uterine fibroids and endometrial cancer, and a novel endometrial cancer genetic risk region at the WNT4 1p36.12 locus - Pik Fang Kho; Sally Mortlock; Frederic Amant; Daniela Annibali; Katie Ashton; John Attia; Paul L. Auer; Matthias W. Beckmann; Amanda Black; Louise Brinton; Daniel D. Buchanan; Stephen J. Chanock; et al. (Human Genetics, 2021)

Seasonal Variations of CH4 Emissions in the Yangtze River Delta Region of China Are Driven by Agricultural Activities - Wenjing Huang; Timothy J. Griffis; Cheng Hu; Wei Xiao; Xuhui Lee (Advances in Atmospheric Sciences, 2021)

World Octopus Fisheries - Warwick H. H. Sauer; Ian G. Gleadall; Nicola Downey-Breedt; Zöe Doubleday; Graham Gillespie; Manuel Haimovici; Christian M. Ibáñez; Oleg N. Katugin; Stephen Leporati; Marek R. Lipinski; Unai Markaida; Jorge E. Ramos; et al. (Reviews in Fisheries Science & Aquaculture, 2021)

Bottom–Up Impacts of Forecasted Climate Change on the Eastern Bering Sea Food Web - George A. Whitehouse; Kerim Y. Aydin; Anne B. Hollowed; Kirstin K. Holsman; Wei Cheng; Amanda Faig; Alan C. Haynie; Albert J. Hermann; Kelly A. Kearney; André E. Punt; Timothy E. Essington (Frontiers in Marine Science, 2021)
Recent observations of record low winter sea-ice coverage and warming water temperatures in the eastern Bering Sea have signaled the potential impacts of climate change on this ecosystem, which have implications for commercial fisheries production. We investigate the impacts of forecasted climate change on the eastern Bering Sea food web through the end of the century under medium- and high-emissions climate scenarios in combination with a selection of fisheries management strategies by conducting simulations using a dynamic food web model. The outputs from three global earth system models run under two greenhouse gas emission scenarios were dynamically downscaled using a regional ocean and biogeochemical model to project ecosystem dynamics at the base of the food web. Four fishing scenarios were explored: status quo , no fishing, and two scenarios that alternatively assume increased fishing emphasis on either gadids or flatfishes. Annual fishery quotas were dynamically simulated by combining harvest control rules based on model-simulated stock biomass, while incorporating social and economic tradeoffs induced by the Bering Sea’s combined groundfish harvest cap. There was little predicted difference between the status quo and no fishing scenario for most managed groundfish species biomasses at the end of the century, regardless of emission scenario. Under the status quo fishing scenario, biomass projections for most species and functional groups across trophic levels showed a slow but steady decline toward the end of the century, and most groups were near or below recent historical (1991–2017) biomass levels by 2080. The bottom–up effects of declines in biomass at lower trophic levels as forecasted by the climate-enhanced lower trophic level modeling, drove the biomass trends at higher trophic levels. By 2080, the biomass projections for species and trophic guilds showed very little difference between emission scenarios. Our method for climate-enhanced food web projections can support fisheries managers by informing strategic guidance on the long-term impacts of ecosystem productivity shifts driven by climate change on commercial species and the food web, and how those impacts may interact with different fisheries management scenarios.

Effects of Electrode Diameter and Contact Material on Signal Morphology of Gastric Bioelectrical Slow Wave Recordings - Abhishek A. Kamat; Niranchan Paskaranandavadivel; Saeed Alighaleh; Leo K. Cheng; Timothy R. Angeli (Annals of Biomedical Engineering, 2020)

Low-pressure–temperature stability of pyrope + quartz relative to orthopyroxene + kyanite: a new model for aluminous orthopyroxene with vacancies - Nanfei Cheng; David M. Jenkins; Timothy J. B. Holland (Contributions to Mineralogy and Petrology, 2019)

Conservation effectiveness of protected areas for Hong Kong butterflies declines under climate change - Wenda Cheng; Timothy C. Bonebrake (Journal of Insect Conservation, 2017)

PM2.5 Exposure Suppresses Dendritic Maturation in Subgranular Zone in Aged Rats - Lewis Cheng; Way K.W. Lau; Timothy K. H. Fung; Benson W.M. Lau; Bolton K.H. Chau; Yutong Liang; Zhe Wang; Kwok Fai So; Tao Wang; Chetwyn C. H. Chan; Tatia M. C. Lee (Neurotoxicity Research, 2017)

Cognitive reserve and cortical thickness in preclinical Alzheimer’s disease - Corinne Pettigrew; Anja Soldan; Yuxin Zhu; Mei-Cheng Wang; Timothy Brown; Michael Miller; Marilyn Albert (Brain Imaging and Behavior, 2017)

Asymmetry, connectivity, and segmentation of the arcuate fascicle in the human brain - Juan C. Fernández-Miranda; Yibao Wang; Sudhir Pathak; Lucia Stefaneau; Timothy Verstynen; Fang-Cheng Yeh (Brain Structure and Function, 2015)

Soil and foliar nutrient and nitrogen isotope composition (δ15N) at 5 years after poultry litter and green waste biochar amendment in a macadamia orchard - Shahla Hosseini Bai; Cheng-Yuan Xu; Zhihong Xu; Timothy J. Blumfield; Haitao Zhao; Helen Wallace; Frédérique Reverchon; Lukas Van Zwieten (Environmental Science and Pollution Research, 2015)

Candidate locus analysis of the TERT–CLPTM1L cancer risk region on chromosome 5p15 identifies multiple independent variants associated with endometrial cancer risk - Luis G. Carvajal-Carmona; Tracy A. O’Mara; Jodie N. Painter; Felicity A. Lose; Joe Dennis; Kyriaki Michailidou; Jonathan P. Tyrer; Shahana Ahmed; Kaltin Ferguson; Catherine S. Healey; Karen Pooley; Jonathan Beesley; et al. (Human Genetics, 2015)

Characterization of ammonia gas release from concrete added with ammoniated fly ash - Lin Shou; Joshua Hayes; Weizhi Cheng; Chang-Yu Wu; Timothy Townsend; Tim Vinson; John Schert (Air Quality, Atmosphere & Health, 2014)

Binding of a dimeric manganese porphyrin to serum albumin: towards a gadolinium-free blood-pool T 1 MRI contrast agent - Weiran Cheng; Tameshwar Ganesh; Francisco Martinez; Jolie Lam; Hyung Yoon; Robert B. Macgregor; Timothy J. Scholl; Hai-Ling Margaret Cheng; Xiao-an Zhang (JBIC Journal of Biological Inorganic Chemistry, 2014)

Automated Algorithm for GI Spike Burst Detection and Demonstration of Efficacy in Ischemic Small Intestine - Jonathan C. Erickson; Raisa Velasco-Castedo; Chibuike Obioha; Leo K Cheng; Timothy R. Angeli; Greg O’Grady (Annals of Biomedical Engineering, 2013)

Risk assessment of polycyclic aromatic hydrocarbons in aquatic ecosystems - Bing Wu; Rui Zhang; Shu-Pei Cheng; Timothy Ford; Ai-Min Li; Xu-Xiang Zhang (Ecotoxicology, 2011)

Genomic aspects of research involving polyploid plants - Xiaohan Yang; Chu-Yu Ye; Zong-Ming Cheng; Timothy J. Tschaplinski; Stan D. Wullschleger; Weilun Yin; Xinli Xia; Gerald A. Tuskan (Plant Cell, Tissue and Organ Culture (PCTOC), 2011)

Response of leaf anatomy of Chenopodium acuminatum to soil resource availability in a semi-arid grassland - Fu-Sheng Chen; De-Hui Zeng; Timothy J. Fahey; Cheng-Yi Yao; Zhan-Yuan Yu (Plant Ecology, 2010)

Serum zinc is decreased in Alzheimer’s disease and serum arsenic correlates positively with cognitive ability - Larry Baum; Iris Hiu Shuen Chan; Stanley Kwok-Kuen Cheung; William B. Goggins; Vincent Mok; Linda Lam; Vivian Leung; Elsie Hui; Chelsia Ng; Jean Woo; Helen Fung Kum Chiu; Benny Chung-Ying Zee; et al. (BioMetals, 2010)

Comparative genomics reveals functional transcriptional control sequences in the Prop1 gene - Robert D. Ward; Shannon W. Davis; MinChul Cho; Constance Esposito; Robert H. Lyons; Jan-Fang Cheng; Edward M. Rubin; Simon J. Rhodes; Lori T. Raetzman; Timothy P. L. Smith; Sally A. Camper (Mammalian Genome, 2007)

Carbon budgeting in plant–soil mesocosms under elevated CO 2 : locally missing carbon? - Weixin Cheng; Daniel A. Sims; Yiqi Luo; Dale W. Johnson; J. Timothy Ball; James S. Coleman (Global Change Biology, 2000)
Summary Studies have suggested that more carbon is fixed due to a large increase in photosynthesis in plant–soil systems exposed to elevated CO 2 than could subsequently be found in plant biomass and soils –‐ the locally missing carbon phenomenon. To further understand this phenomenon, an experiment was carried out using EcoCELLs which are open‐flow, mass‐balance systems at the mesocosm scale. Naturally occurring 13 C tracers were also used to separately measure plant‐derived carbon and soil‐derived carbon. The experiment included two EcoCELLs, one under ambient atmospheric CO 2 and the other under elevated CO 2 (ambient plus 350 μL L − 1 ). By matching carbon fluxes with carbon pools, the issue of locally missing carbon was investigated. Flux‐based net primary production ( NPP f ) was similar to pool‐based primary production ( NPP p ) under ambient CO 2 , and the discrepancy between the two carbon budgets (12 g C m − 2 , or 4% of NPP f ) was less than measurement errors. Therefore, virtually all carbon entering the system under ambient CO 2 was accounted for at the end of the experiment. Under elevated CO 2 , however, the amount of NPP f was much higher than NPP p , resulting in missing carbon of approximately 80 g C m − 2 or 19% of NPP f which was much higher than measurement errors. This was additional to the 96% increase in rhizosphere respiration and the 50% increase in root growth, two important components of locally missing carbon. The mystery of locally missing carbon under elevated CO 2 remains to be further investigated. Volatile organic carbon, carbon loss due to root washing, and measurement errors are discussed as some of the potential contributing factors.